2018
DOI: 10.1186/s12930-018-0041-2
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes and beliefs of general practitioners towards clinical practice guidelines: a qualitative study in Al Ain, United Arab Emirates

Abstract: BackgroundThe efficacy of implementing practices based on the best evidence is determined by the limitations and preparedness of the structure and processes of the healthcare system as well as healthcare professionals’ (HCP) levels of knowledge and acceptance. Facilitating implementation of such practices also partly depends on HCPs’ attitudes.MethodWe investigate the attitudes and beliefs of four groups of physicians in the United Arab Emirates on clinical practice guidelines (CPGs), with a focus on applying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Physicians revealed that their current practices and choices on whether or not to use available international clinical guidelines when treating primary insomnia depended on knowledge of and resistance to guidelines, the presence of barriers limiting their use, and the lack of facilitators to encourage adherence to the stipulated guidelines. Although some of the themes identified in this study are similar to those discussed in previous studies [1618], no research, to the best of the authors’ knowledge, has identified physicians’ resistance to implementing international guidelines as a principal theme.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Physicians revealed that their current practices and choices on whether or not to use available international clinical guidelines when treating primary insomnia depended on knowledge of and resistance to guidelines, the presence of barriers limiting their use, and the lack of facilitators to encourage adherence to the stipulated guidelines. Although some of the themes identified in this study are similar to those discussed in previous studies [1618], no research, to the best of the authors’ knowledge, has identified physicians’ resistance to implementing international guidelines as a principal theme.…”
Section: Discussionsupporting
confidence: 66%
“…There is little qualitative research in the Middle East about the knowledge, perceptions and attitudes of general practitioners towards clinical practice guidelines (CPGs) that can help to facilitate implementation of good practice. A recent study in the United Arab Emirates, found that practitioners had a positive attitude towards CPGs and welcomed the use of evidence-based practice that is supported by electronic medical records, persistent quality monitoring and structured care programmes [18]. Participants, however, also expressed negative attitudes towards impractical guidelines, inconsistent recommendations among guidelines and the possibility of ‘changing evidence’ [18].…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 presents the results of the quality assessment of the qualitative studies. The purposive snowballing sampling technique was used in four studies [16][17][18][19], whereas two studies targeted clinicians in specific hospitals [14,15]. Although the cited studies adequately described the selection of participants, no information was provided on the recruitment process, such as the original number invited and those who declined.…”
Section: Study Quality Assessmentmentioning
confidence: 99%
“…For instance, two studies presented the topic guides as Supplementary Materials [14,19], one adequately described the topic guide content [16], one described the method used to build the topic guide [15], and four discussed the saturation of data [16][17][18][19]. Analysis was conducted using a thematic framework [17][18][19], grounded theory analysis [16], and qualitative content analysis [14], whereas one study did not report the method used for analysis. The main concern regarding the quality of qualitative studies was that although rigorous, data analysis specifically failed to address the role of the researchers and point out potential bias during the formulation of research questions and data collection including sample recruitment and the rationale for deriving themes from the data.…”
Section: Study Quality Assessmentmentioning
confidence: 99%
“…Based on AGREE II, two expert consensus received low scores, generally between 4 and 57%, and four domains scored less than 50%, especially in the “Editorial Independence” and “Rigor of Development” domains. As a matter of fact, clinical staffs always regard guidelines as valuable and trustworthy, and they are more likely to make decisions in accordance with recommendations based on a systematic review of the evidence [38, 39]. So evidence-based guidelines are essentially needed.…”
Section: Discussionmentioning
confidence: 99%